Analisis ANALYSIS OF THE SIMARJARUNJUNG AREA'S POTENTIAL FOR INCREASING MICRO, SMALL, AND MEDIUM ENTERPRISES (MSME) INCOME - Roeskani Sinaga; Linda Reni S Purba; Citra Situmorang Pratomo (Prodi Agribisnis Fakultas Agro Teknologi Universitas Prima Indonesia, 2025)
Analysis of the Potential of the Simarjarunjung Region for Increasing MSME Income. The research was conducted in February-March 2025 in Simarajarunjung Nagori Parik Sabungan, Dolok Pardamean District, Simalungun Regency. There were 30 respondents in this study, consisting of 15 visitors and 15 MSME entrepreneurs in Simarjarunjung. The objectives of the study were (1) to identify the potential of the Simarjarunjung area that can be developed to increase MSME income, (2) to address the challenges faced by MSME in Simarjarunjung in developing their businesses, and (3) to formulate appropriate strategies for developing MSME in Simarjarunjung to increase community income. The research method used was qualitative research, with data collection employing both primary and secondary data. Data analysis methods include validity and reliability tests to answer hypothesis 1 and SWOT analysis to answer hypotheses 2 and 3. The research results show that the validity tests for attraction, accessibility, and accommodation concluded that all calculated r values were greater than the table r values, thus deemed valid. However, in the validity test for ancillary factors, there were 4 statements, where 3 statements had r calculated > r table, thus deemed valid, while 1 statement had r calculated < r table, thus deemed invalid. The reliability test showed that the alpha value of all variables was greater than the reference value of >0.60, thus concluding that all statements were reliable. The research results using SWOT analysis showed that based on IFE and EFE calculations, the total scores were 1.13 and 1.01, respectively. Furthermore, in the SWOT diagram, it was in quadrant 1, where the Simarjarunjung area had greater strengths and opportunities than weaknesses and threats. The conclusion of this study is that SMEs in Simarjarunjung have regional potential that can be leveraged to increase MSME income in Simarjarunjung, such as natural beauty, strategic location, attractive photo spots, and major festivals. However, they also have weaknesses and limitations, such as limited capital, similar attractions, inadequate public transportation access to the Simarjarunjung region, insufficient MSME promotion, and the SWOT matrix to determine MSME strategies in Simarjarunjung.